2015
DOI: 10.3389/fpsyg.2015.01239
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind in women with borderline personality disorder or schizophrenia: differences in overall ability and error patterns

Abstract: Although borderline personality disorder (BPD) and schizophrenia (SZ) are notably different mental disorders, they share problems in social cognition—or understanding the feelings, intentions and thoughts of other people. To date no studies have directly compared the social cognitive abilities of individuals with these two disorders. In this study, the social cognitive subdomain theory of mind was investigated in women with BPD (n = 25), women with SZ (n = 25) and healthy women (n = 25). An ecologically valid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 46 publications
4
51
0
2
Order By: Relevance
“…Social cognition may be defined as the ability to infer another's thoughts, feelings, and intentions (Frith & Frith, ); thus, the construct of social cognition highly overlaps with the constructs of theory of mind (ToM; Woodruff, Premack, & Kennel, ) and mentalizing (Frith & Frith, ). Against this background and consistent with previous reports (e.g., Ha, Sharp, Ensink, Fonagy, & Cirino, ; Sharp et al, ; Vaskinn et al, ), in this study, we used the term social cognition as a synonym of mentalizing and ToM .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Social cognition may be defined as the ability to infer another's thoughts, feelings, and intentions (Frith & Frith, ); thus, the construct of social cognition highly overlaps with the constructs of theory of mind (ToM; Woodruff, Premack, & Kennel, ) and mentalizing (Frith & Frith, ). Against this background and consistent with previous reports (e.g., Ha, Sharp, Ensink, Fonagy, & Cirino, ; Sharp et al, ; Vaskinn et al, ), in this study, we used the term social cognition as a synonym of mentalizing and ToM .…”
Section: Introductionsupporting
confidence: 56%
“…Against this background and consistent with previous reports (e.g., Ha, Sharp, Ensink, Fonagy, & Cirino, 2013;Sharp et al, 2011;Vaskinn et al, 2015), in this study, we used the term social cognition as a synonym of mentalizing and ToM.…”
Section: Introductionmentioning
confidence: 64%
“…Our fourth perspective is on the primary and explicit aim of the MBT therapist – to maintain a joint focus on mentalizing and mentalizing deficits in therapy. In the present study sample, although we cannot report measures of the patients’ mentalizing capacity, the BPD patients with severe personality pathology in PDT and MBT are likely to be a comparable cohort with poor personality functioning and severe mentalizing deficits (Antonsen et al ., ; Vaskinn et al ., ). It is noteworthy that MBT‐PDT outcome differences were largest among these patients and conceivable that an intervention style explicitly focusing on mentalizing deficiencies could be important.…”
Section: Discussionmentioning
confidence: 97%
“…Borderline personality disorder (BPD) is known to be a heterogeneous disorder of variable clinical severity (Johansen, Karterud, Pedersen, Gude, & Falkum, 2004). Patients with BPD typically present with characteristic interpersonal vulnerability, emotional instability, and a disturbed capacity to interpret and reflect over mental states (mentalization) (Antonsen, Johansen, Ro, Kvarstein, & Wilberg, 2016;Diamond et al, 2014;Vaskinn et al, 2015). Several studies have shown that the extent of maladaptive personality features, not only within BPD, but also across personality disorder (PD) categories, is closely related to the severity of social impairment and symptom distress among patients Kvarstein & Karterud, 2012Newton-Howes, Tyrer, & Weaver, 2008;Yang, Coid, & Tyrer, 2010).…”
mentioning
confidence: 99%
“…Although the mentalizing process was initially described in autism spectrum disorder and schizophrenia (Baron-Cohen, Leslie, & Frith, 1985;Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001;Fernández-Abascal, Cabello, Fernández-Berrocal, & Baron-Cohen, 2013;Gavilán-Ibáñez & García-Albea, 2013), is not limited to them. Indeed, in relation BPD, some specific patterns can differ [e.g., under-mentalizing vs. over-mentalizing (Andreou et al, 2015;Vaskinn et al, 2015)].…”
Section: Introductionmentioning
confidence: 99%